Biochar-Enhanced Resistance to Botrytis cinerea in Strawberry Fruits (But Not Leaves) Is Associated With Changes in the Rhizosphere Microbiome - De Tender, Caroline; Vandecasteele, Bart; Verstraeten, Bruno; Ommeslag, Sarah; Kyndt, Tina; Debode, Jane (Frontiers in Plant Science, 2021)
Biochar has been reported to play a positive role in disease suppression against airborne pathogens in plants. The mechanisms behind this positive trait are not well understood. In this study we hypothesized that the attraction of plant growth promoting rhizobacteria (PGPR) or fungi (PGPF) underlies the mechanism of biochar in plant protection. The attraction of PGPR and PGPF may either activate the plant’s innate immune system or help the plant with nutrient uptake. We studied the effect of biochar in peat substrate on susceptibility of strawberry, both on leaves and fruit, against the airborne fungal pathogen Botrytis cinerea. Biochar had a positive impact on the resistance of the strawberry fruit but not the plant leaves. On leaves, the infection was more severe compared to plants without biochar in the peat substrate. The different effect on fruit and plant leaves may indicate a trade-off between plant parts. Future studies should focus on monitoring gene expression and metabolites of strawberry fruits to investigate this potential trade-off effect. A change in the microbial community in the rhizosphere was observed as well, with an increased fungal diversity and higher abundances of ASVs classified as Granulicella, Mucilaginibacter and Byssochlamys surrounding the plant root, the latter two reported as biocontrol agents. The change in microbial community was not correlated with a change in nutrient uptake by the plant in either the leaves or the fruits. A decrease in the defense gene expression in the leaves was observed. In conclusion, the decreased infection of B. cinerea in strawberry fruit mediated by biochar addition in peat substrate is most likely regulated by changes in the microbial community.